The effect of central contracts on the stability and performance of the England Test cricket team. [El efecto de contratos centrales sobre la estabilidad y el desempeño del equipo inglés de Test cricket]. - Steven Bullough; Robbie Millar; Girish Ramchandani; Richard Coleman (Ramón Cantó Alcaraz, 2014)
In 1999 the England and Wales Cricket Board (ECB) decided to implement central contracts for elite player management to give them control over a group of players to represent the England national team in Test cricket. The purpose of this paper is to investigate the impact that this change in policy has had on the stability and performance of the England Test team, and discuss implications thereof. Using a sample of 13 seasons pre-central contracts (1987-1999) and 13 seasons post-central contracts (2000-2012), the results, from secondary analysis of England's Test match scorecards from both sample periods, allowed investigation of team performance and stability. To gain a greater understanding of how central contracts impacted on the England Test side, eight interviews were also organised with key stakeholders in English cricket. The results showed that both the stability and performance of the England Test side improved considerably in the sample period post-central contracts (2000-2012) with a much greater consistency of selection (fewer changes per match) alongside an improvement in England's on-field performance (better win ratio and points per match). The paper identifies two key challenges facing the current player management system in England from domestic and external sources. Resumen En 1999 El Consejo de Cricket en Inglaterra y Gales (ECB - England and Wales Cricket Board) decidió implementar contratos centrales para la dirección de jugadores de élite, con el fin de darle control sobre el grupo de jugadores que representan el equipo nacional de Inglaterra de Test cricket. El objetivo de este artículo es investigar el impacto que este cambio ha tenido sobre la estabilidad y el desempeño del equipo inglés de Test cricket y considerar sus implicaciones. Tras emplear una muestra de 13 temporadas antes de la firma de los contratos centrales (entre 1987 y 1999) y otras 13 temporadas después de su implementación (entre 2000 y 2012), los resultados provenientes del análisis de los tanteadores indican estabilidad. Para comprender mejor el impacto de los contratos centrales sobre el equipo, realizamos asimismo 8 entrevistas con depositarios importantes en el mundo del Test cricket en Inglaterra. Los resultados mostraron que la estabilidad y el desempeño del equipo mejoraron considerablemente en el periodo de muestra después de la introducción de contratos centrales (2000-2012) con más regularidad en la selección de los jugadores (menos cambios en cada partido) además de una mejora en el desempeño del equipo durante los partidos (ganaron más partidos y anotaron más puntos en cada partido). El artículo, por tanto, identifica dos retos claves a los que se enfrenta la gestión actual de los jugadores en Inglaterra (de fuentes internas y externas).